ELECTROPHORETIC HAEMOLYMPH PROTEIN PATTERN IN A FEW BIVOLTINE RACES OF THE SILKWORM, BOMBYX MORI - BAKKAPPA, SHIVA KUMAR; G. SUBRAMANYA (The Bioscan, 2010)
The objective of this study is to understand the genetic difference between six bivoltine races useful for silkworm hybridization. The haemolymph proteins of V instar 2nd day larvae were analyzed utilizing six bivoltine races by SDS-PAGE. Based on the commassie brilliant blue pattern, the protein fractions were classified into three groups, I, II and III. The high molecular weight fractions were grouped under I, whereas II and III were included under moderate and low molecular weight fractions respectively. All the three groups fall in the range of 29 kDa to 97.4 kDa. The results have clearly indicated, the differentially expressed protein banding pattern in the six bivoltine races with highest number of 31 bands were observed in P31 race (Bione, European race), whereas 24 bands were evident in C108 race (Chinese race). Based on the UPGMA dendrogram the genetic distance between the races was established.